Estimating soil carbon sequestration with woody and bamboo biochar using the Japanese Industrial Standard (JIS) M 8812 - Yasuji Kurimoto; Ayaka Wenhong Kishimoto-Mo; Takeshi Kajimoto; Fumihiro Ozawa; Akira Shibata (Carbon Management)
The Intergovernmental Panel on Climate Change (IPCC) established a methodology to estimate carbon sequestered from biochar additions to mineral soils in the 2019 Refinement Guideline, requiring a pyrolysis temperature exceeding 350 °C and three variables: organic carbon content in fraction (Fc), fraction of biochar carbon remaining after 100 years (Fperm), and biochar mass. Japan has reported biochar amendments in its national greenhouse gas inventory since 2020 using default IPCC values. However, Japan has traditionally evaluated biochar properties based on Japanese Industrial Standard (JIS) M 8812, which measures fixed carbon (FC), volatile matter (VM), and ash content. This study developed a protocol to convert the JIS parameters to the IPCC variables Fc and Fperm for woody and bamboo biochar. We established a VM/FC-based power approximation expression to estimate pyrolysis temperature, and derived a conversion equation from the liner relationship between JIS values, organic carbon content (Corg, %) and Fperm. Inventory country-specific values for woody and bamboo biochar were proposed, with Fc (Fc = Corg/100) and Fperm reflecting three pyrolysis temperature levels. This conversion protocol enables practical, cost-effective application to diverse biochar feedstocks, supporting country-specific variable development and broader biochar use for carbon dioxide removal.